2018
DOI: 10.1007/s13197-018-3172-4
|View full text |Cite
|
Sign up to set email alerts
|

Acyl-homoserine-lactones receptor LuxR of Shewanella baltica involved in the development of microbiota and spoilage of refrigerated shrimp

Abstract: Numerous bacterial species utilize quorum sensing molecules acyl-homoserine-lactones (AHLs) to communicate, however, crosstalk often complicates the dynamics and behaviors of mixed populations. In this study, we developed a mutant of wild type SA03 (WT SA03), and aimed to investigate the role of LuxR (AHLs receptor) involved in the spoilage of refrigerated shrimp () by inoculating WT SA03 and mutant of SA03 ( SA03), respectively. The results indicated the maximum growth rate of total viable bacteria in shrimp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The effect of different AHLs on the bacterial growth was evaluated according to the method of Jie et al (2018). Overnight culture of P. fluorescens (OD 600 = 1) was diluted at 1:100 ratio in fresh LB broth containing 2 μg/mL of different AHLs (C 4 -HSL, C 6 -HSL, C 8 -HSL, C 10 -HSL, C 12 -HSL, and C 14 -HSL), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of different AHLs on the bacterial growth was evaluated according to the method of Jie et al (2018). Overnight culture of P. fluorescens (OD 600 = 1) was diluted at 1:100 ratio in fresh LB broth containing 2 μg/mL of different AHLs (C 4 -HSL, C 6 -HSL, C 8 -HSL, C 10 -HSL, C 12 -HSL, and C 14 -HSL), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Microaerobic conditions are favourable to these bacteria, they act on the degradation of organic matter and impact various cycles of matter due to their versatile respiratory network. The genus was shown to be implicated in the degradation of micro-and macroorganisms (Dos Santos et al 1998;Nealson and Scott 2006;Richards et al 2008;Kakizaki et al 2009;Skrlin et al 2011;Janda and Abbott 2014;Petit et al 2015;Martin et al 2015;Jie et al 2018;Yagi et al 2018). Organic matter degradation provides formate, lactate or pyruvate, simple or complex sugars, fatty acids, nucleosides, amino acids, osmolytes or more exotic organic compounds that are all used as carbon, nitrogen, and phosphorus sources but also to sustain a diversified and adaptable respiratory network (Fig.…”
Section: Carbon and Energetic Metabolism: Consequences On Ecological mentioning
confidence: 99%
“…Bacteria-bacteria interactions have also been underlined in work dealing with the recycling of organic matter (Jie et al 2018;Zhu et al 2018) Indeed, it has been shown that the quorum sensing mechanism is important for Shewanella growth during degradation of refrigerated fish. However, the Shewanella strain from this study can sense the signal molecule from quorum sensing but it cannot produce it (Jie et al 2016).…”
Section: Prokaryotesmentioning
confidence: 99%
“…It's widely believed that QS can regulate bacteria growth and metabolism, such as Pseudomonas aeruginosa (Flickinger et al 2011) and Shewanella baltica (Jie et al 2018). PLA production levels may be relevant to the complicated energy transduction (glucose metabolism), different enzyme system and the influence of peptide supply and cosubstrate (Vermeulen et al 2006;Mu et al 2012).…”
Section: Optical Images Of the Microcapsules Of Lplantarum Ab-1mentioning
confidence: 99%